Reducing vehicle heating, ventilation and air conditioning noise using low-cost and biodegradable natural materials from coconut fiber absorber - Muhammad Zulkarnain; M. Sobron Yamin, Lubis; Darmawan, Steven; Ariyanti, Silvi; Bakri, Mohd Badzli; Veza, Ibham (Faculty of Engineering, Universitas Indonesia, 2024)
The heating, ventilation, and air conditioning (HVAC) units in vehicles can produce significant noise, lowering the sound quality inside the vehicle and reducing passenger comfort. While noise control methods are available, they can be expensive and harmful to the environment. To address these issues, this study aims to investigate using low-cost and biodegradable natural materials, specifically coconut fibers, for vehicle HVAC noise control. The study utilized coconut fibers, which have sound absorption properties reaching 42 dBA, to treat an actual Perodua HVAC unit. The treatment targeted the HVAC noise spectrum at low, medium, and high blower speeds, resulting in reduced Sound Pressure Levels (SPL) at the passenger's ear position. The composite was applied to the air inlet head and inlet channel of the HVAC system using a specific combination of coconut fiber content. The research identified the sources of noise in the highest contributions that occurred at the blower fan unit and treated the required areas. In terms of numerical data, the results showed that the treatment significantly reduced the noise level by 11 dBA. Additionally, the experiment found that the 8% fiber ratio at low speed decreased by 14.28% following the treatment. Similarly, the fiber ratio at medium and high speeds saw reductions of 15.47% and 17.56%, respectively. This study presents a promising solution for reducing noise in vehicle HVAC units using cost-effective and eco-friendly materials. Future research should focus on optimizing coconut fiber ratios, evaluating long-term durability and biodegradability, validating real-world applicability, and establishing standardized testing protocols to improve and confirm the effectiveness of coconut fiber-based noise control in automotive HVAC systems.